Exopolysaccharidic matrix from biological soil crusts from arctic environments - Rossi F; Mugnai Gianmarco; Colica Giovanni; Ventura Stefano; Sili Claudio; Mascalchi Cristina; De Philippis Roberto (2012)
Environmental Engineering and Management Journal March 2012, Vol.11, No. 3, Supplement, S162 http://omicron.ch.tuiasi.ro/EEMJ/ “Gheorghe Asachi” Technical University of Iasi, Romania P102 EXOPOLYSACCHARIDIC MATR IX OF BIOLOGICAL SOIL CRUSTS FROM ARTIC ENVIRONMENTS Federico Rossi 1 , Gianmarco Mugnai 1 , Giovanni Colica 1 , Stefano Ventura 2 , Claudio Sili 2 , Cristina Mascalchi 2 , Roberto De Philippis 1 1 Department of Agricultural Biotechnology, University of Florence, Florence, Italy; 2 Institute for Ecosystem Studies, CNR, Florence, Italy Abstract Biological soil crusts (BSC) are soil-surface communities that repr esent a typical example of microbial adaptability to harsh environmental conditions. They im prove soil fertility and promote plant growth, representing a valid putative tool to fight desertification processes. Various mechanis ms allow them to withstand constraints such as drought, high solar irradiation and wind erosion. These organisms produce extracellular polyme ric substances (EPS), excret ed in response to the envi ronmental characteristics, which are known to primarily contribute in ma ny ways to the increase of constraint to lerance. While various features of these excreted molecules have been investigated in axenic bacteria l cultures, a not definitive and re latively low number of studies c ome from the direct study of the entire matrix of microbial aggregat es, with limitative information on how they contribute to micro bial survival in extreme environments. The aim of this study was to investigate the microbial compos ition and the characteristics, both qualitative and quantitative, of the EPS extracted from BSC collected by several sites in Ny- Ǻ lesund, Svalbard Island, Norway, in a landscape mostly characterized by the high arctic tundra, where environm ental conditions are extreme and where BSC play a key role in creating a favorable habitat for plant growth af ter deglaciation processes. A proper method for extracting EPS directly from the crust samp les was optimized. ...